Limonene Detection in the Exhaled Human Breath Providing an Early Diagnosis Method of Liver Diseases - Erich Kny; Christoph Kleber; Wiktor Luczak (Chemosensors)
This review aims to summarize possible methods for the detection of limonene in the gas phase at low to very low concentrations. Limonene has historically been of interest as a fragrance in cosmetics, the food industry, pharmaceutics, and the production of solvents. The development of analytical methods for limonene was initially driven by its use in relevant industries such as chemical, pharmaceutics, cosmetics, food, agriculture, and forestry. More recently, it has been recognized as a potent biomarker for human metabolic conditions, such as liver disease and certain cancers. The interest in improved limonene detection in exhaled human breath has increased, particularly from the medical field, which demands high reliability, very low detection limits in the parts per billion (ppb) and even parts per trillion (ppt) range, and excellent selectivity against other exhaled volatile organic compounds (VOC). In addition, the detection methods should be portable and affordable to facilitate potential mass screening. This review paper aims to explore all possible detection methods by evaluating their proven analytical capabilities for limonene or discussing their potential usefulness, benefits, and applicability for limonene detection.